Moderate to Vigorous-intensity Continuous Training versus Highintensity Interval Training for Improving VO2max in Women: A Systematic Review and Meta-analysis - Lindner, Robert; Raj, Isaac Selva; Yang, Angela Wei Hong; Zaman, Shadman; Larsen, Brianna; Denham, Joshua (International Journal of Sports Medicine, 2023)
Traditional continuous training and high-intensity interval training (HIIT) can increase maximal oxygen uptake (V̇O2max). However, there is conflicting evidence regarding which form of training demonstrates the greatest improvements to V̇O2max, and data in women is sparse. We conducted a systematic review and meta-analyses to assess whether moderate to vigorous-intensity continuous training (MVICT) or HIIT was superior at improving V̇O2max in women. Randomised controlled and parallel studies examined the influence of MVICT and/or HIIT on V̇O2max in women. There was no statistical difference in V̇O2max improvements after training between women in the MVICT and HIIT cohorts (mean difference [MD]: −0.42, 95%CI: −1.43 to 0.60, p>0.05). Both MVICT and HIIT increased V̇O2max from baseline (MD: 3.20, 95% CI: 2.73 to 3.67 and MD: 3.16, 95% CI 2.09 to 4.24, respectively, p<0.001). Greater improvements in V̇O2max were observed in women who participated in more training sessions in both training formats. Long-HIIT was superior to short-HIIT protocols at increasing V̇O2max. Although MVICT and long-HIIT sessions elicited greater increases in V̇O2max in younger women compared to short-HIIT protocols, these differences were negligible in older women. Our findings suggest MVICT and HIIT are equally effective strategies for improving V̇O2max and indicate an effect of age on its response to training in women.
Keywords: HIIT; exercise; female; athlete development; maximal oxygen uptake; endurance training; MVICT